An Analysis of Factors of Student Interest in English Language SB Sentul Malaysia - Bella Sukma Suwanda; Ana Maghfiroh; Diyah Atiek Mustikawati; Shohenuddin (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2023)
One of the things that makes students learn English is interest. Interest in English makes students want to learn it. The purpose of this research is to analyze the factors that influence students' interest in English language. This study used a qualitative descriptive interview method where the research was conducted by interviewing students outside the classroom by taking as many as 5 respondents who were students at Sanggar Bimbingan Sentul, Malaysia. As a result, students are interested in learning English because they want to continue their higher education, because they are more comfortable communicating with friends who speak English, and because the school demands it, so it becomes a habit and results in interest.